Water Resource Policy Analysis and Stakeholder Involvement in Water Security - Pertamsari, Rismanitia; Munandar, Adis Imam (Journal of Governance and Public Policy, 2020)
In accordance with the ratification of the Water Resource Law, which was established after Law Number 7 of 2004 is canceled by the Constitutional Court in 2015, water has now becoming fully controlled by the state through the Law no. 17/2019 concerning Water Resource Law. The identification of emerging interests on who would advantage from the use of water are not only coming from the communities but also from the various stakeholders. The method used in this journal is theoretical qualitative as basis for discussion and analysis. The purpose of this journal is to examine thoroughly the part of the policy which addressing water compliance, water security with an increasing threat on water crimes and water conflicts and involving stakeholders in enforcing the sustainability of water management upon the enactment of the latest Water Resource law.